Long-term statin therapy is associated with severe coronary artery calcification. - Kyari Sumayin Ngamdu; Dhairyasheel S Ghosalkar; Hojune E Chung; Jared L Christensen; Cadence Lee; Celia A Butler; Tiffany Ho; Alice Chu; Jacob R Heath; Muhammad Baig; Wen-Chih Wu; Gaurav Choudhary; et al. (PLoS ONE, 2023)
Background Atherosclerosis and consequent risk of cardiovascular events or mortality can be accurately assessed by quantifying coronary artery calcium score (CACS) derived from computed tomography. HMG-CoA-reductase inhibitors (statins) are the primary pharmacotherapy used to reduce cardiovascular events, yet there is growing data that support statin use may increase coronary calcification. We set out to determine the likelihood of severe CACS in the context of chronic statin therapy. Methods We established a retrospective, case-control study of 1,181 U.S. veterans without coronary artery disease (CAD) from a single site, the Providence VA Medical Center. Duration of statin therapy for primary prevention was divided into 5-year categorical increments. The primary outcome was CACS derived from low-dose lung cancer screening computed tomography (LCSCT), stratified by CACs severity (none = 0; mild = 1-99; moderate = 100-399; and severe ≥400 AU). Statin duration of zero served as the referent control. Ordinal logistic regression analysis determined the association between duration of statin use and CACS categories. Proportional odds assumption was tested using likelihood ratio test. Atherosclerotic cardiovascular disease (ASCVD) risk score, body mass index, and CKD (glomerular filtration rate of <60 ml/min/1.73 m2) were included in the adjustment models. Results The mean age of the study population was 64.7±7.2 years, and 706 (60%) patients were prescribed a statin at baseline. Duration of statin therapy was associated with greater odds of having increased CACS (>0-5 years, OR: 1.71 [CI: 1.34-2.18], p<0.001; >5-10 years, OR: 2.80 [CI: 2.01-3.90], p<0.001; >10 years, OR: 5.30 [CI: 3.23-8.70], p<0.001), and the relationship between statin duration and CACS remained significant after multivariate adjustment (>0-5 years, OR: 1.49 [CI: 1.16-1.92], p = 0.002; >5-10 years, OR: 2.38 [CI: 1.7-3.35], p<0.001; >10 years, OR: 4.48 [CI: 2.7-7.43], p<0.001). Conclusions Long-term use of statins is associated with increased likelihood of severe CACS in patients with significant smoking history. The use of CACS to interpret cardiovascular event risk may require adjustment in the context of chronic statin therapy.